Cross-sectional study of bovine anaplamosis in South-western Uganda : the impact of wildlife-livestock interface - Palmfjord, Mikael (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2015)
The tick-borne disease bovine anaplasmosis is primarily caused by Anaplasma marginale. A variety of wild animals act as reservoirs for A. marginale, but the understanding of their role in the epidemiology of A. marginale is yet poor. This cross-sectional study was conducted to establish if proximity of wildlife affect the prevalence of bovine anaplasmosis in cattle. A total of 130 cattle were randomly sampled from two sampling areas within Kiruhura district, South-western Uganda. Sampling sites were chosen due to their distinct proximity to Lake Mburo National Park, resulting in one area with frequent and one with infrequent wildlifelivestock interface. Both sero-prevalence, using an indirect ELISA (Svanova Biotech AB Uppsala, Sweden) and microscopically determined prevalence, based on examination of Giemsa-stained blood smears, were established. Agreement between both diagnostic tests was compared using microscopy as golden standard. To estimate the wildlife-livestock interface and to rank the role of tick-born diseases (TBD) as a constraint to livestock production a questionnaire was used. Furthermore, ticks were collected to estimate the relationship between tick burden and the A. marginale prevalence. Statistical analyses was performed using Pearson’s χ2-test and Fisher’s exact tests at a significance level of α = 0.05. There was a significant difference in how frequent the livestock interacted with wildlife in the two sampling areas, which confirms the choice of sampling areas. A significantly higher seroprevalence was found in the area with a more frequent wildlife-livestock interface. This difference was not found microscopically. Sero-prevalence reflects the situation over time, rather than the momentarily picture obtained by microscopy, which could explain the difference seen. In relation to our hypothesis, we think that sero-prevalence provides more reliable results. Confounders, such as age of the animal, grazing system and tickburden, that potentially could explain the observed difference between the sampling areas did not significantly influence sero-prevalence. Concluding, A. marginale sero-prevalence increases with a more frequent wildlife-livestock interface. There was a disagreement between the diagnostic methods, which was confirmed by a low sensitivity and specificity comparing these tests. Further validation of the ELISA test is needed, preferably by use of molecular methods. No correlation between tick burden and A. marginale prevalence was found, which could be due to the use of an unstandardized tick sampling method. The overall low sero-prevalence of 24.6 (± 7.4) % and relatively high microscopical prevalence of 30.8 (± 7.29) % indicates endemic instability to bovine anaplasmosis in Kiruhura district. These findings are consistent with recent studies in Uganda showing a growing problem of TBD, including A. marginale and should serve as an indicator for possible future interventions in the area.